Mechanical rotational chair-assisted multiple canalith repositioning procedures for benign paroxysmal positional vertigo: enhanced vertigo relief, comparable adverse effects, and decreased incidence of residual dizziness - Zhang, Hao; Zhu, Meijia (Frontiers in Neurology, 2023)
Objectives: This retrospective study aimed to assess the effectiveness and adverse effects of mechanical rotational chair-Assisted multiple canalith repositioning procedures (CRPs)to treat benign paroxysmal positional vertigo (BPPV).A retrospective analysis of 1,273 BPPV patients was conducted, with 241 patients included in the final study. The participants diagnosed with BPPV, unresolved by a single previous CRP, were categorized into either the single or multiple CRPs groups. In both groups, on days 1, 4, and 7 after the initial treatment, the participants were reevaluated after a single CRP; if positional vertigo were resolved, the treatment was regarded as successful. The remission rate, adverse effects (such as canal switch (CS), falls, vomiting), residual dizziness (RD) rate, RD duration were compared between the two groups.The resolution rates for the single and multiple CRPs groups were significantly different on days 1 and 4 (55.7% vs 85.1%, 75.5% vs 91.9%; P<0.05), but not on day 7 (93.3% vs 94.8%; P>0.05). There were no significant differences between the single and multiple CRPs groups in terms of CS and falls (3.8% vs 5.2%, 10.3% vs 8.9%; P > 0.05). However, there was a significant difference in the incidence of vomiting (6.6% vs 14.8%; P < 0.05). RD such as Head heaviness, imbalance, and nonspecific dizziness are more common in the single CRP group than in the multiple CRPs group (34.9% vs 20.7%, 42.5% vs 26.7%, 47.2% vs 32.6%; P<0.05). The incidence and duration of RD were notably diminished in the group undergoing multiple CRPs compared to the single-CRP group, with incidence rates of 41.5% and 57.5%, respectively (P<0.05).For patients with BPPV, multiple CRPs offer greater benefits than a single CRP.